2017
DOI: 10.4103/1319-2442.215126
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of end-stage renal disease in Dubai: Single-center data

Abstract: Hemodialysis (HD) was first established in Dubai in the year 1980 and was in its full capacity by the year 1983. Since then, the HD population has been growing rapidly. This report represents the demographic data and clinical characteristics of our HD patients during the period between January 2012 and October 2016. Diabetic nephropathy (57%) and hypertension (12.4%) are emerging as the most common causes of end-stage renal disease (ESRD) in our data, followed by undetermined causes in those who presented as E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Results of this study are presented in tables and figures and broadly summarized into 2 categories: desk research (Tables 1 [9][10][11][12][13][14][15][16][17] and 2 10,[18][19][20][21] , Figure 1, and Supplementary Table S1) and survey administration (Figures 2-5 and Supplementary Figures S1-S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of this study are presented in tables and figures and broadly summarized into 2 categories: desk research (Tables 1 [9][10][11][12][13][14][15][16][17] and 2 10,[18][19][20][21] , Figure 1, and Supplementary Table S1) and survey administration (Figures 2-5 and Supplementary Figures S1-S5).…”
Section: Resultsmentioning
confidence: 99%
“…Data on the prevalence of treated KF were available for only 8 of the 13 countries in the region (Table 2). [18][19][20] All 3 modes of KRT (long-term HD, PD, and kidney transplantation) were available from most countries; Saudi Arabia (826 pmp) and the United Arab Emirates (152 pmp) reported the highest and lowest prevalence of treated KF in the region, respectively. Lebanon reported the highest prevalence of HD (668.5 pmp), whereas Qatar reported the highest prevalence of long-term PD (104.5 pmp), although the prevalence of long-term HD was still more than twice as high in Qatar (296.4 pmp), indicating a preference of HD over PD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the style of living, increase in incident chronic diseases lead to a high complication. There is a significant association between Glomerulonephritis and other urinary tract infection with incident of ESRD which was confirmed by several studies conducted in different countries [32][33][34][35][36]. The associations of different cut-off values of serum creatinine with the risks of death from any causes, particularly with the cardiovascular events have been examined in several studies [37][38][39][40][41].…”
Section: Analytical Proceduresmentioning
confidence: 61%
“…Similarly, Alalawi et al . have also reported that 57% and 12.4% of the ESRD cases resulted from diabetic nephropathy and hypertension, respectively [ 26 ]. It has also been reported that anxiety and depression are associated with ESRD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%